0578 Clinical Patterns of Obstructive Sleep Apnea patients in COVID 19. (25th May 2022) - Mechineni, Ashesha; Gardner, Jessica; Gordon, Howard; Prasad, Bharati
Abstract: Introduction: Recent studies indicate Obstructive Sleep Apnea (OSA) patients have higher severity of respiratory compromise after COVID19 infection due to their sleep related hypoxemic burden. The pro-inflammatory state associated with OSA, sympathetic excitation, and recurrent hypoxemia may predispose to poorer post-COVID19 outcomes. We compared COVID19 infection outcomes in a cohort of hospitalized Veterans with and without OSA. Methods: We used Jesse Brown Veteran Affairs Medical Center (JBVAMC) Registry for Research on Risk Factors and Outcomes of Veterans Evaluated for COVID19. The registry includes all patients who received a test for COVID19 at JBVAMC through November 8th, 2021. Data are from the VA COVID19 Shared Data Resource and chart review, and include demographic data, pharmacological and non-pharmacological interventions, clinical outcomes, and pre-existing conditions. The study was approved by the Institutional review board (IRB). STATA v16 was used for data analysis. Results: Of the 13, 385 patients included in the registry, 1890 patients were found to have a positive COVID19 test, of which 625 were hospitalized and included in our study. The sample was older (mean age of 66.8 years), predominantly men (583, 93.3%) and African Americans (461, 73.8%). 18.7% (117, 18.7%) were European American, and (47, 7.5%) were of other race categories. The group with OSA was 37.8% (n=236) and without OSA was 62.2% (n=389) of the total sample. Elixhauser comorbidity index was higher in OSA group compared to those without OSA (p:0.00001, mean (SD): 16.73(14.6) vs. 12.03 (13.1)). Univariate analysis demonstrated a higher rate of readmission at 60 days (p=0.02, Odds ratio (95% CI): 1.69 (1.1-2.6)) and use of mechanical ventilation (p=0.05, Odds ratio (95% CI): 1.65 (0.99-2.75) in OSA vs. without OSA. These associations were attenuated in multivariate logistic regression models including age, gender, race, Elixhauser index and body mass index. OSA did not affect the length of stay or inpatient mortality. Conclusion: In hospitalized COVID19 patients, OSA increases the probability of readmission and risk of mechanical ventilation, but this effect is likely due to higher comorbidity and obesity rates in OSA. In the future, we plan to examine larger samples of Veterans hospitalized with COVID19 and assess the effect of positive airway pressure treatment to understand the impact of OSA on COVID19 outcomes. Support (If Any): no conflicting or financial interests to disclose